A LINGUISTIC COMPARISON OF ENGLISH AND UZBEK IDIOMATIC EXPRESSIONS - Erkinova Hilola Alisher qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This paper aims to compare and contrast idiomatic expressions in English and Uzbek languages. Idioms, as fixed expressions, convey figurative meanings that are culturally rooted. The study explores similarities and differences in idiomatic expressions, offering insights into how language reflects the cultural backgrounds of its speakers. Through a comparative analysis, the research reveals that although some idioms have equivalent counterparts in both languages, many others are unique to each language, influenced by historical, cultural, and social factors. The paper highlights the challenges in translating idioms and emphasizes the importance of understanding idiomatic expressions for language learners and translators. The study contributes to the field of linguistics by enhancing our understanding of the relationship between language, culture, and communication.